The effects of tape insert material on the flow and heat transfer in a nanofluid-based double tube heat exchanger: Two-phase mixture model. (June 2019) - Karimi, Ali; Al-Rashed, Abdullah A.A.A.; Afrand, Masoud; Mahian, Omid; Wongwises, Somchai; Shahsavar, Amin
Highlights: Simulation of nanofluid in a heat exchanger equipped with twisted tape using a two-phase mixture model. Studying effect of nanofluid and twisted tape on the thermal performance of heat exchanger. Evaluating effect of material type of twisted tape on heat transfer and pressure drop in the heat exchanger. The use of twisted tape improved the Nusselt number up to 22%. Alumina nanoparticles increased heat transfer and pressure drop up to 30% and 40%, respectively. Abstract: The present study dealt with the numerical simulation of nanofluid flow in a double tube heat exchanger equipped with twisted tape. Alumina/water nanofluid and pure water are considered to be working fluids. A two-phase mixture model was employed for nanofluid flow simulation. The effect of nanofluid and twisted tape on the hydrodynamic and thermal performance of the heat exchanger was studied. Next, the focus was placed on the effect of the surface roughness (material type) of twisted tape on heat transfer and pressure drop in the heat exchanger. The results are presented as the temperature distribution, velocity field, Nusselt number, and pressure drop for various Reynolds numbers, nanofluid concentrations, pitch ratios, and tape insert materials. The results revealed that the use of twisted tape improved the Nusselt number up to 22%; also, adding alumina particles to water augmented heat transfer up to 30% and increased pressure drop up to 40%. Tapes with more roughness provided heat transfer enhancement of up to 16%, whereas the friction factor increased up to 21%. Graphical abstract: Image, graphical abstract